2022
DOI: 10.1021/acsfoodscitech.1c00274
|View full text |Cite
|
Sign up to set email alerts
|

Complexed Biopolymer of Whey Protein and Carboxymethyl Cellulose to Enhance the Chemical Stability of Lemon Oil-in-Water Emulsions

Abstract: Lemon oil (LO) has been used as a flavoring food additive and its encapsulation in emulsions has facilitated its incorporation in food and pharmaceutical products. D-Limonene, the main ingredient in LO, and citral, the compound responsible for the aromatic profile, are easily oxidized and a new emulsion interfacial structure is needed to protect these compounds. This paper studies the physical and chemical stabilities of LO-in-water emulsions produced by membrane emulsification as a function of the oil droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Additionally, the energy values of the highest occupied molecular orbital show that E HOMO limonene is "in the middle" of the tested monoterpenes and allow for the ranking of the examined compounds from the most reactive ones, respectively: thymol, pienene, limonene, cymene, and menthol. These calculations are partially confirmed by experimental data [14,32]. The use of the solvent model does not significantly affect the structures of the analyzed monoterpenes.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Additionally, the energy values of the highest occupied molecular orbital show that E HOMO limonene is "in the middle" of the tested monoterpenes and allow for the ranking of the examined compounds from the most reactive ones, respectively: thymol, pienene, limonene, cymene, and menthol. These calculations are partially confirmed by experimental data [14,32]. The use of the solvent model does not significantly affect the structures of the analyzed monoterpenes.…”
Section: Discussionsupporting
confidence: 73%
“…It is known that limonene undergoes oxidation and degradation in an acidic environment. In order to limit this process, various stabilizers such as whey protein and an electrostatic whey protein-carboxymethyl cellulose complex were used [14]. Nevertheless, a change in the research environment and tests of toilet waters containing limonene showed its high stability [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor contributing to their stability is the presence of a polysaccharideprotein complex in the system, which imparts favorable interfacial properties and further aids in stabilization. In line with this, Kaade et al (2022) demonstrated that the chemical stability of D-limonene-containing emulsions can be improved by employing a complex of whey protein and Carboxymethyl Cellulose (CMC). However, the effect of this complex on the physicochemical properties and stability of carotenoid-containing emulsions remains unknown.…”
Section: Introductionmentioning
confidence: 77%